(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To evaluate the therapeutic outcomes and identify factors associated with treatment failure for vaginitis in women aged 40 years and older at the Department of Obstetrics and Gynecology, Binh Duong General Hospital. Subjects and methods: The prospective cohort study without a control group with follow-up included 152 patients (aged 40+) diagnosed with vaginitis due to at least one of three agents: bacteria, fungi, or Trichomonas. Results: Among 152 patients, the majority fell within the 40–49 age group (75.7%). The study population was characterized by a high urban residency rate (82.9%) and a predominance of industrial workers, who accounted for 51.3% of the total sample. Additionally, 75.7% of the participants were identified as being in the perimenopausal stage. The 2-week total microbiological clearance rate (negative for both clinical symptoms and microbiological tests) was 69.7%. The efficacy in the mixed infection group was lower than in the single infection group (54.2% vs. 72.7%). Analysis of the treatment failure group identified behavioral barriers as the primary contributors. Medication non-adherence or premature cessation was associated with a nearly 28-fold surge in the risk of treatment failure (aOR = 27.69). Concurrently, improper vaginal insertion technique significantly elevated this risk by nearly eightfold (aOR = 7.58) relative to the compliant group. At the 3-month follow-up, the sustained cure rate was 77.4%, with the highest recurrence observed in the mixed infection group (30.8%), primarily due to the persistence of the index pathogens rather than reinfection. Conclusions: The treatment regimen achieved a total microbiological clearance rate of 69.7%; however, this outcome faced significant hurdles from mixed infections (achieving only 54.2%) and behavioral execution errors. The study identified that medication non-adherence and incorrect insertion techniques were the primary drivers of treatment failure, with adjusted odds ratios of 27.69 and 7.58, respectively. Therefore, implementing visual counseling and personalized medication technique guidance, combined with the management of occupational hygiene factors, is a pivotal strategy to enhance sustained cure rates and minimize the risk of recurrence—currently reaching 30.8% in the mixed infection group—for women over 40.